Heavily Indebted Poor Countries (HIPC) Initiative and Multilateral Debt Relief Initiative (MDRI) : Status of Implementation 2009. (Policy Papers; Policy Paper, 2009)
This paper updates the status of implementation, impact, and costs of the Enhanced Heavily Indebted Poor Country (HIPC) Initiative and the Multilateral Debt Relief Initiative (MDRI). Debt relief provided under the Initiatives has substantially alleviated debt burdens in recipient countries. Aided by continued flexibility on the part of IDA and the Fund, substantial progress has been achieved under the Initiatives since the last report, and a number of post-decision-point countries have already benefited from debt relief.